Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1063/1.1514385
|View full text |Cite
|
Sign up to set email alerts
|

Superintegrability with third-order integrals in quantum and classical mechanics

Abstract: We consider here the coexistence of first-and third-order integrals of motion in two dimensional classical and quantum mechanics. We find explicitly all potentials that admit such integrals, and all their integrals. Quantum superintegrable systems are found that have no classical analog, i.e. the potentials are proportional toh 2 , so their classical limit is free motion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
225
0
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(236 citation statements)
references
References 31 publications
1
225
0
9
Order By: Relevance
“…24 It was shown that in the case of one first-order and one third-order integral, the only classical superintegrable systems were known ones ͑like V = ␣r 2 or V = ␣r −1 ͒ for which the third-order integral was the product, on the Poisson commutator, of a first-and second-order one. However, in the quantum case, a new superintegrable potential of this type exists, namely V 1 ͑x , y͒ = ͑ប ͒ 2 k 2 sn 2 ͑ x , k͒, where sn͑ x , k͒ is a Jacobi elliptic function.…”
Section: ͑14͒mentioning
confidence: 99%
See 2 more Smart Citations
“…24 It was shown that in the case of one first-order and one third-order integral, the only classical superintegrable systems were known ones ͑like V = ␣r 2 or V = ␣r −1 ͒ for which the third-order integral was the product, on the Poisson commutator, of a first-and second-order one. However, in the quantum case, a new superintegrable potential of this type exists, namely V 1 ͑x , y͒ = ͑ប ͒ 2 k 2 sn 2 ͑ x , k͒, where sn͑ x , k͒ is a Jacobi elliptic function.…”
Section: ͑14͒mentioning
confidence: 99%
“…The classical limit ͑ប → 0͒ is free motion! 24 All classical and all quantum potentials allowing a second-order integral of the form ͑1.2͒ and a third-order integral ͑of any form ͒ were found in Ref. 25.…”
Section: ͑14͒mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic study of superintegrable classical and quantum systems with a third order integral is more recent. 8,9 All classical and quantum potentials with a second and a third order integral of motion that separate in Cartesian coordinates in the twodimensional Euclidean space were found in Ref. 9.…”
Section: Rational Function Potentials I Introductionmentioning
confidence: 99%
“…Linear integrals of motion be obtained from exact Noether symmetries and quadratic integrals from Hamilton-Jacobi (Schrödinger) separability but third-order integrals must be obtaining by other alternative procedures; because of this, the number of known integrable systems admitting cubic in the momenta constants is very limited [9,10,13,21,23]. For n = 2 we can point out the Fokas-Lagerstrom and the Holt potentials for the Euclidean plane [8,12], and three of the Drach potentials for the pseudoeuclidean plane [16,19].…”
Section: Third-order Integralsmentioning
confidence: 99%